Quality-controlled characterization of a monoclonal antibody specific to an EC5-domain of human desmoglein 3 for pemphigus research - Eming, Rüdiger; Riaz, Shafaq; Müller, Eliane J.; Zakrzewicz, Anna; Linne, Uwe; Tikkanen, Ritva; Zimmer, Christine Lea; Hudemann, Christoph (Frontiers in Immunology, 2024)
Pemphigus vulgaris (PV) is a life-threatening autoimmune blistering disease caused mainly by IgG autoantibodies (auto-abs) against the cadherin-type adhesion molecules desmoglein (Dsg) 1 and 3. Pathogenic anti-Dsg3 auto-abs bind to different Dsg3 epitopes, leading, among others, to signalling that is involved in pathogenic events, such as Dsg3 depletion. As central tools in research on PV, a limited number of antibodies such as AK23 are frequently used by the autoimmune bullous disease community. Previously, we have introduced a novel Dsg3 EC5-binding antibody termed 2G4 that may potentially serve as a superior tool for numerous PV related analysis. The purpose of this study was to develop a quality-controlled production and verification process that allows I) a continuous quality improvement, and II) a verified and comprehensible overall quality with regard to pathogenic antigen-specific binding in a variety of pemphigus assays for each batch production. Thus, a workflow based on a standardized operating procedure was established. This includes the verification of purity and in-vitro binding capacity (SDS-page, direct and indirect immunofluorescence) as primary parameters, and size analysis by mass-spectrometry and ex-vivo pathogenicity by monolayer dissociation assay. We here present an extensive point-by-point quality controlled IgG production protocol, which will serve as a basis for a standardized antibody assessment in PV research.